Antimicrobial resistance and phylogenetic lineages of KPC-2-producing blood-borne Klebsiella pneumoniae subsp. pneumoniae from Kolkata, India during 2015–2024: Emergence of Klebsiella pneumoniae subsp. pneumoniae with blaKPC-2, blaNDM, and blaOXA-48-like triple carbapenemases - Gourab Halder; Bhaskar Narayan Chaudhuri; Balaji Veeraraghavan; Priyanka Denny; Paulami Dutta; Mandira Chakraborty; Ujjwayini Ray Khan; Shelley Sharma Ganguly; Subhranshu Mandal; Yesha Parasmani Upadhyaya; Bedobroto Biswas; Arindam Chakraborty; et al. (Microbiology Spectrum)
ABSTRACT In view of insufficient data on the epidemiology and genomics of blaKPC-2 producing Klebsiella pneumoniae subsp. pneumoniae (KPC-2 Kpn) from India, this study, first of its kind, was conducted to characterize blood-borne KPC-2 Kpn isolates according to their resistome, plasmid types, and genotypes. This study included 45 blood-borne KPC-2 Kpn isolates from ICU-admitted sepsis patients in Kolkata from 2015 to 2024. These isolates were tested for antibiotic susceptibility against ≥10 antimicrobial classes. Antimicrobial resistance gene profiles, genetic environment of blaKPC-2, plasmid types, MLST genotypes, and virulence genes were determined by whole-genome shotgun sequencing (WGS). The transmissibility of blaKPC-2 genes was evaluated by conjugation experiment. Pulsed-field gel electrophoresis (PFGE) was conducted to confirm their clonality. SNP-based phylogenomic analysis was performed to compare the study isolates with global KPC-2 Kpn isolates. All 45 (100%) KPC-2 Kpn isolates showed resistance to 21 antimicrobials. In addition, 55.55% and 33.33% isolates were resistant to colistin and ceftazidime-avibactam, respectively. Presence of triple carbapenemase (blaKPC-2, blaNDM-1/5 and blaOXA-181/232) was observed in six isolates. blaKPC-2 transferable by IncFII/IncFII(pBK30683)/ColRNAI conjugative plasmids. WGS identified two distinct genetic environments of blaKPC-2 among the isolates based on presence or absence of Tn4401. PFGE identified 45 pulsotypes with a 39.3% similarity coefficient, indicating a variety of infection sources. Of the 16 MLST genotypes found in circulation, ST15 was predominant and ST7485 was novel. Hypervirulent genetic markers (iucA, iutA, and rmpA2) were identified in four isolates. Hospital infection control and surveillance programs should be strengthened to detect and combat K. pneumoniae co-harboring blaKPC-2 and/or blaNDM and/or blaOXA-48-like carbapenemase.IMPORTANCEKlebsiella pneumoniae (Kpn) is the primary etiology of ICU-related bloodstream infections in India. Multi-drug resistance, including resistance to carbapenems and colistin, along with myriad virulence factors, makes this bacterium really troublesome with respect to effective treatment. In India, blaNDM and blaOXA-48-like carbapenemases are the most prevalent types with only sporadic reports of blaKPC in Kpn. This study focuses on the emergence of blaKPC-2 in Kpn along with other carbapenemases in Kolkata, India. This study is also the first of its kind to describe the presence of triple carbapenemase (blaKPC-2, blaNDM-1/5 and blaOXA-181/232) and concurrent resistance to carbapenems, colistin, and ceftazidime-avibactam antimicrobials in Kpn. In addition, this study also highlights the diverse genotypes (sequence types) identified in KPC-2 Kpn, including the novel ST7485 identified in this study. Routine monitoring of antimicrobial resistance genes in Kpn should be encouraged to identify the emerging resistome, which will aid in determining the most effective treatment.